عجز الموازنة العامة في دول العالم الثالث وأساليب معالجته ( حالة خاصة القطر العربي السوري ) - الخليل, فـادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر عجز الموازنة العامة في الدول النامية من أكثر المشكلات خطورة والتي تتعرض لها اقتصادات هذه الدول، نتيجة التطبيق الخاطئ للنظرية الكينزية وللدور الذي يمكن أن تلعبه الدولة في توجيه النشاط الاقتصادي حيث أن نمو الإنفاق العام في هذه الدول لم يقابله نمو مماثل في الإيرادات العامة مما أوقعها في مشكلة: كيفية التمويل، والذي سعت لتحقيقه بطرق خاطئة سواء بالاقتراض الخارجي أو الداخلي أو بالتمويل التضخمي مما فاقم الأزمة ولم يعالجها، ولذلك فإن عرض أسباب العجز وأساليب معالجته سيكون موضوع هذا البحث. Deficit of master Budgets in the developing countries is one of the most dangerous problems that the economies of these countries face due to wrong application of the Kenzis Theory, and the role supposed to be played by the state in guiding the economical activity; the growth of the national revenue in these countries was not paralleled with the increase in the national expenditure. this led to financing problems, the thing that these countries tried to overcome in many wrong methods, either by external or local borrowing or by inflationary financing which by its turn complicated the problem and did not solve it. Therefore, the exhibition of deficit causes and the methods of handling them will be the topic of this research.